Antitumor Effects and Mechanism of Novel Emodin Rhamnoside Derivatives against Human Cancer Cells In Vitro - Xing, Jie-yu; Song, Gao-peng; Deng, Jun-peng; Jiang, Ling-zhi; Xiong, Ping; Yang, Bin-jie; Liu, Shan-shan (PLOS ONE, 2015)
A series of novel anthracene L-rhamnopyranosides compounds were designed and synthesized and their anti-proliferative activities on cancer cell lines were investigated. We found that one derivative S-8 (EM-d-Rha) strongly inhibited cell proliferation of a panel of different human cancer cell lines including A549, HepG2, OVCAR-3, HeLa and K562 and SGC-790 cell lines, and displayed IC50 values in low micro-molar ranges, which are ten folds more effective than emodin. In addition, we found EM-d-Rha (3-(2”,3”-Di-O-acetyl-α-L-rhamnopyranosyl-(1→4)-2’,3’-di-O-acetyl-α-L-rhamnopyranosyl)-emodin) substantially induced cellular apoptosis of HepG2 and OVCAR-3 cells in the early growth stage. Furthermore, EM-d-Rha led to the decrease of mitochondrial transmembrane potential, and up-regulated the express of cells apoptosis factors in a concentration- and time-dependent manner. The results indicated the EM-d-Rha may inhibit the growth and proliferation of HepG2 cells through the pathway of apoptosis induction, and the possible molecular mechanism may due to the activation of intrinsic apoptotic signal pathway.